An association between sleep quality and functional status among older people in agricultural plantation - Makhtar, Aniawanis; Syed Elias, Sharifah Munirah; Zurkefili, Siti Zurshaira (Kulliyyah of Allied Health Sciences, International Islamic University Malaysia, 2019)
The phenomena of the ageing population all over the world, including Malaysia, bring a significant impact on the wellbeing of older people. The sleep deviation happens at older people with the increasing of their age. Older people may face other health complication due to sleep deterioration. The purpose of this study was to determine the association between functional status and sleep quality among older people in the agricultural plantation. In a cross-sectional study, 245 subjects were selected by convenience sampling from one agricultural plantation in Malaysia. The instruments used in this study included the Pittsburgh Sleep Quality Index (PSQI), Barthel Index, list of questions about sociodemographic data and self-reported medical conditions. Data were encoded, entered onto a computer, and analysed with SPSS 22.0 software. The mean age of respondents was 69 years (SD=5.443) with a range of age from 60 to 85. It was found that the majority of respondents had poor sleep quality (64.5%) in comparison with good sleep quality (35.5%). Sociodemographic factors (age, gender, marital status and educational level), comorbid condition (hypertension, diabetes, pulmonary disease and musculoskeletal disease) and functional status were associated with sleep quality. Respondents with totally dependency functional status had more percentage of having poor sleep quality. The result indicated the important role of functional status on sleep quality among older people. Health care providers are responsible for assessing the level of independence to preserve and control the quality of sleep among older people